On Foreign Shareholdings and Agency Costs: New Evidence from China. Issue 12 (26th September 2018) - Hai, Jiang; Min, Huang; Barth, James R.
ABSTRACT: This article examines the impact of foreign shareholdings on agency costs of Chinese firms from 2006 to 2012. The empirical results indicate that: (1) direct foreign shareholdings, in contrast to indirect foreign shareholdings, improve asset utilization, suggesting low agency costs; (2) qualified foreign institutional investors play a significant role in firms because they are less subject to political pressure, which is consistent with lower agency costs, but this effect could be eroded by government control; and (3) foreign shareholdings reduce the cost of equity and improve firm performance. The results contribute to the privatization of state-owned enterprises and the domestic/foreign ownership structure of firms.